2016
DOI: 10.1091/mbc.e15-12-0851
|View full text |Cite
|
Sign up to set email alerts
|

Sorting nexin 27 couples PTHR trafficking to retromer for signal regulation in osteoblasts during bone growth

Abstract: The endocytic protein SNX27 functions to link the parathyroid hormone receptor (PTHR) to the retromer trafficking complex. Loss of SNX27 in mice leads to overactive PTHR signaling and reduced osteoblastic bone formation during postnatal bone growth. Thus SNX27 is a new modulator of PTHR signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 85 publications
(114 reference statements)
4
60
1
Order By: Relevance
“…Finally, because the experiments were of necessity performed with PTHR overexpression, we cannot conclude with certainty whether ASRT or ASRT-independent recycling predominates under physiological conditions. While the present study was under review, a complementary investigation reported compatible findings that additionally demonstrate an important role of SNX27 on PTH actions on skeletal development (88). Global SNX27 knock-out decreased multiple parameters of bone architecture in post-natal mice.…”
Section: Discussionsupporting
confidence: 76%
“…Finally, because the experiments were of necessity performed with PTHR overexpression, we cannot conclude with certainty whether ASRT or ASRT-independent recycling predominates under physiological conditions. While the present study was under review, a complementary investigation reported compatible findings that additionally demonstrate an important role of SNX27 on PTH actions on skeletal development (88). Global SNX27 knock-out decreased multiple parameters of bone architecture in post-natal mice.…”
Section: Discussionsupporting
confidence: 76%
“…This PDZ ligand assumes a Type I consensus sequence (E-T-V-M) that is compatible with the canonical recognition signature of the SNX27-PDZ domain. Parallel studies recently confirmed this engagement, thereby providing a direct molecular link to the ASRT complex [50, 63]. First, a PDZ-dependent interaction was demonstrated between PTHR and SNX27 by combining coimmunoprecipitation studies in HEK293 cells with isothermal titration calorimetry (ITC), the later titrating a series of native and mutant PTHR-PDZ-ligand peptides against the SNX27-PDZ domain.…”
Section: Asrt-mediated Endosome-to-plasma Membrane Recyclingmentioning
confidence: 95%
“…Ablation of β 2 AR suppressed expression of PTH-target genes involved in bone turnover. Further evidence that sustained PTHR signaling is required for normal skeletal development comes from studies showing the interfering with receptors internalized to endosomes in osteoblasts reduces bone mineralization and causes major skeletal deficits [50], as discussed below.…”
Section: What’s In It For Me?mentioning
confidence: 99%
See 1 more Smart Citation
“…SNX27 is directly bound to the retromer subunit VPS26 and simultaneously binds to a multitude of PDZ-and tyrosine-based sorting motifs in the cytosolic tail of its cargo proteins, thereby driving their recycling back to the cell surface (Steinberg et al, 2013;Gallon et al, 2014;Ghai et al, 2013). Retromer and SNX27 have been shown to recycle a wide range of surface molecules, ranging from signalling receptors like the β2-adrenergic receptor (Lauffer et al, 2010) or the parathyroid hormone receptor (PTHR) (Chan et al, 2016;McGarvey et al, 2016), and nutrient transporters (Steinberg et al, 2013) to neuronal glutamate receptors (Wang et al, 2013;Loo et al, 2014;Hussain et al, 2014). Although loss of retromer as well as of the WASH complex is lethal early in embryogenesis (Wen et al, 2011;Gomez et al, 2012), loss of SNX27 is lethal shortly upon birth of genetically modified mice (Cai et al, 2011), highlighting the physiological relevance of SNX27-, retromer-and/or WASH-driven recycling processes.…”
Section: Introductionmentioning
confidence: 99%